Probiotic Lactobacillus plantarum Promotes Intestinal Barrier Function by Strengthening the Epithelium and Modulating Gut Microbiota - Wang, Jing; Ji, Haifeng; Wang, Sixin; Liu, Hui; Zhang, Wei; Zhang, Dongyan; Wang, Yamin (Frontiers in Microbiology, 2018)
Weaning disturbs the intestinal barrier function and increases the risk of infection in piglets. Probiotics exert beneficial health effects, mainly by reinforcing the intestinal epithelium and modulating the gut microbiota. However, the mechanisms of action, and especially, the specific regulatory effects of modulated microbiota by probiotics on the intestinal epithelium have not yet been elucidated. The present study aimed to decipher the protective effects of the probiotic Lactobacillus plantarum strain ZLP001 on the intestinal epithelium and microbiota as well as the effects of modulated microbiota on epithelial function. Paracellular permeability was measured with fluorescein isothiocyanate-dextran (FD-4). Gene and protein expression levels of tight junction (TJ) proteins, proinflammatory cytokines, and host defense peptides were determined by RT-qPCR, ELISA, and western blot analysis. Short-chain fatty acid (SCFA) concentrations were measured by ion chromatography. Fecal microbiota composition was assessed by high-throughput sequencing. The results showed that pretreatment with 108 colony forming units (CFU) mL−1 of L. plantarum ZLP001 significantly counteracted the increase in gut permeability to FD-4 induced by 106 CFU mL−1 enterotoxigenic Escherichia coli (ETEC). In addition, L. plantarum ZLP001 pretreatment alleviated the reduction in TJ proteins (claudin-1, occludin, and ZO-1) and downregulated proinflammatory cytokines IL-6 and IL-8, and TNFα expression and secretion caused by ETEC. L. plantarum ZLP001 also significantly increased the expression of the host defense peptides pBD2 and PG1-5 and pBD2 secretion relative to the control. Furthermore, L. plantarum ZLP001 treatment affected piglet fecal microbiota. The abundance of butyrate-producing bacteria Anaerotruncus and Faecalibacterium was significantly increased in L. plantarum ZLP001-treated piglets, and showed a positive correlation with fecal butyric and acetic acid concentrations. In addition, the cell density of Clostridium sensu stricto 1, which may cause epithelial inflammation, was decreased after L. plantarum ZLP001 administration, while the beneficial Lactobacillus was significantly increased. Our findings suggest that L. plantarum ZLP001 fortifies the intestinal barrier by strengthening epithelial defense functions and modulating gut microbiota.